Effective Specific Activity Dilution in Labeled DNA of Cultured Mammalian Cells (L5178Y) - Burki, H. John (1969)
Upon labeling the DNA of cultured mammalian cells with radio-active thymidine it was found that there was a large reduction in the specific activity of radioactive thymidine in DNA when this specific activity was compared to the specific activity of the exogenous supply. This reduction in specific activity may be determined once the effective dilution factor for thymidine in mammalian cells is known. The average effective dilution factor was found to be 2 × 10(-4) M for L5178Y cells in log growth.